Shelf Life of short ripened soft Cheese Stored under Various Packaging Conditions. Issue 6 (15th August 2012) - Marcuzzo, Eva; Peressini, Donatella; Sensidoni, Alessandro
Abstract Stracchino is a short ripened soft cheese mainly produced in the North of Italy. The changes in Stracchino cheese quality are mainly attributable to microbial spoilage and structure breakdown because of enzymatic activity. The aim of this work was to evaluate the effect of different packaging materials on the shelf life of Stracchino cheese, monitoring changes in rheological, microbiological and sensorial properties over 28 days at 4C. Three packaging materials were compared in order to optimize the suitable packaging for Stracchino cheese: (1) paper‐polyethylene as a reference package commonly used for this product [R]; (2) commercial high‐density polyethylene (HDPE) ‐based film, mainly composed of calcium carbonate and HDPE (Ovtene® [OV]); and (3) experimental active packaging obtained with addition of potassium sorbate to OV (active Ovtene® [AOV]). The OV and AOV resulted more effective to control microbial spoilage than R, without affecting sensorial and chemical properties. AOV allowed the inhibition of yeast growth, probably because of the activity of potassium sorbate. The gel structure, which characterizes the Stracchino cheese, was maintained until 21 days with the application of AOV, while a liquid‐like behavior was associated to the sample packed with the reference material after 14 days. Microbiological, rheological and sensory results demonstrated the effectiveness of AOV in prolonging Stracchino cheese storability. Practical Applications In the last years, the research in food packaging have been focused on the development of active packaging, able to interact with food and surrounding media. These innovative materials could be applied in order to extend shelf life of food products. The application of films with potassium sorbate to a short ripened soft cheese resulted effective to maintain product structure and to control microbial spoilage. Active packaging selected in this study could be used as packaging material for this type of cheese in order to prolong shelf life.